Cardiac and Renal Effects of Atrasentan in Combination with Enalapril and Paricalcitol in Uremic Rats - Cynthia Ritter; Sarah Zhang; Jane L. Finch; Helen Liapis; Edu Suarez; Leon Ferder; James Delmez; Eduardo Slatopolsky (Karger Publishers, 2014)
Background/Aims: The search for new therapies providing cardiorenal protection in chronic kidney disease (CKD) has led to treatments that combine conventional renin-angiotensin-aldosterone-system inhibitors with other drugs that exhibit potential in disease management. Methods: In rats made uremic by renal ablation, we examined the effects of addition of the endothelin-A receptor antagonist atrasentan to a previously examined combination of enalapril (angiotensin converting enzyme inhibitor) and paricalcitol (vitamin D receptor activator) on cardiac and renal parameters. The effects of the individual and combined drugs were examined after a 3-month treatment. Results: A decrease in systolic blood pressure, serum creatinine and proteinuria, and improvement of renal histology in uremic rats were attributed to enalapril and/or paricalcitol treatment; atrasentan alone had no effect. In heart tissue, individual treatment with the drugs blunted the increase in cardiomyocyte size, and combined treatment additively decreased cardiomyocyte size to normal levels. Perivascular fibrosis was blunted in uremic control rats with atrasentan or enalapril treatment. Conclusions: We found distinct cardiac and renal effects of atrasentan. Combination treatment with atrasentan, enalapril and paricalcitol provided positive effects on cardiac remodeling in uremic rats, whereas combination treatment did not offer further protective effects on blood pressure, proteinuria or renal histology.